Analisis Transaksi Jizāf dalam Perspektif Qur’an dan Hadis - Maulidya Mora Matondang; Nawir Yuslem; M. Jamil (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
Buying and selling activities are one aspect of muamalah which is very important in human life and receives great attention in the Qur'an and hadith. The principles of justice and honesty are the main foundation in every transaction, as illustrated in the verses which emphasize the importance of correct measures and scales, as in the words of Allah SWT: "Make measures and scales fairly, and do not harm people in their rights" (QS. Al-A'raf [7]: 85). This verse not only emphasizes the need to uphold justice in measurable transactions, but also raises the issue of interpretation regarding the status of transactions that do not use formal measures or scales, such as buying and selling jizāf. In community practice, buying and selling jizāf—that is, buying and selling goods based on estimates without measuring or weighing—has been known since the time of the Prophet Muhammad. A number of hadiths narrate the permissibility of this form of transaction in certain contexts, such as buying and selling foodstuffs or harvests that can be measured in a general sense without causing gharar (unclarity). However, differences in socio-economic contexts and modern trading systems raise a new question: to what extent can the sharia principle, which emphasizes fairness in measurement, be applied to sales without a fixed measure? From an exegetical perspective, classical commentators such as Al-Qurtubi, Ibn Kathir, and Al-Razi have differing emphases in their understanding of verses concerning measures and weights. Some emphasize moral aspects and universal justice, while others emphasize strict legal aspects regarding sales practices. Meanwhile, in the hadith literature, differences in wording and context of the narrations regarding jizāf have given rise to debates about the validity and scope of its permissibility. The hermeneutic tension between the texts of verses that demand precise measurements and the hadith that permit jizāf is an important area of ​​research.